A thermodynamic equilibrium analysis on oxidation of methane to higher hydrocarbons - Saidina Amin, Nor Aishah; Soon, Ee Peng (2007)
Thermodynamic chemical equilibrium analysis using total Gibbs energy minimization method was carried out for methane oxidation to higher hydrocarbons. For a large methane conversion and also a high selectivity to higher hydrocarbons, the system temperature and oxygen concentration played a vital role whereas, the system pressure only slightly influenced the two variables. Numerical results showed that the conversion of methane increased with oxygen concentration and reaction temperature, but decreased with pressure. Nevertheless, the presence of oxygen suppressed the formation of higher hydrocarbons that mostly consisted of aromatics, but enhanced the formation of hydrogen. As the system pressure increased, the aromatics, olefins and hydrogen yields diminished, but the paraffin yield improved. Carbon monoxide seemed to be the major oxygen-containing equilibrium product from methane oxidation whilst almost no H2O, CH30H and HCOH were detected although traces amount of carbon dioxide were formed at relatively lower temperature and higher pressure. The total Gibbs energy minimization method is useful to theoretically analyze the feasibility of methane conversion to higher hydrocarbons and syngas at the selected temperature and pressure.